DSCL and GSCL in ETSI M2M platform - Valente, André Gonçalo Sabino (2015)
Machine to Machine (M2M) is a technology facing huge expansion in the coming years. One can claim that digital technological breakthroughs have changed modern society and the way it interacts with the surroundings. The decreasing prices of sensors/actuators have led to a completely new way of managing industry. The abundance of existing networks, has revolutionized the way a company can check, provide and regulate information about his product. A concept that we must take into account and is very often associated with M2M communications is the Internet of Things, the purpose of this approach is to connect billions of objects and take advantage of their functions as many times as intended. This dissertation will have its focus on developing components for an architecture node M2M. It will focus on certain critical components like the Device Service Capabilities Layer (DSCL), belonging to ETSI M2M architecture according to TS 120 690 standard. These components are traditionally called sensor nodes, in this document technical requirements and limitations are going to be faced aiming a final design.